ANALISIS ASUHAN KEPERAWATAN INTERVENSI TERAPI SLOW STOKE BACK MASSAGE UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI DI RSPAD GATOT SOEBROTO - Mutiara Novella (2023)
Hypertension or high blood pressure is one of the factors that can be at high risk of causing death worldwide. The incidence of hypertension every year always increases because patients run an unhealthy lifestyle and symptoms that cannot be felt. Uncontrolled hypertension can lead to serious complications. Patients need pharmacological companion therapy to be able to lower blood pressure, namely non-complementary therapy. One complementary therapy that can be applied is Slow Stroke Back Massage The purpose of this intervention is to analyze the effectiveness of Slow Stroke Back Massage (SSBM) therapy on reducing blood pressure in hypertensive patients at the emergency room of Gatot Soebroto Hospital. After doing the intervention of Slow Stroke Back Massage therapy once, showed changes in blood pressure before and after, namely systole decreased by 16 mmHg and dyastole blood pressure by 14 mmHg. Based on this analysis, it can be concluded that Slow Stroke Back Massage therapy can reduce blood pressure in hypertensive patients.